Trade unions : on youtube online revitalization in sweden (2019)
This chapter briefy describes the goal and general argument of the book, along with its theoretical framework and data collection, and introduces the Swedish case. First, we set the discussion of labour movements’ trade union revitalization and usage of social media—and particularly of YouTube—into the broader context of scholarly literature. Second, we introduce the Swedish case and compare the videos uploaded by Swedish trade unions with those uploaded by trade union confederations in other European countries. We also explain why we are investigating trade unions representing different social classes—namely, the working class, middle class and upper middle class. Third, we briefy describe the data collection and coding process and explain the methods of analysis used in this book: the rough metadata-based analysis of all videos uploaded by Swedish trade unions to YouTube during the period 2007–2017 (a total of 4535 videos), the detailed qualitative content analysis of 624 randomly selected videos and a qualitative analysis of 60 videos